Der Widerstand gegen Literatur: Dekonstruktive Lektüren zur Literaturdidaktik - Baum, Michael (transcript, 2018)
Michael Baum asks about the contradictions of the literature didactics discourse, which claims to be able to orient successful pedagogical action.